The first Doppler imaging of the active binary prototype RS Canum Venaticorum. Issue 3 (25th January 2020) - Xiang, Yue; Gu, Shenghong; Wolter, U; Schmitt, J H M M; Cameron, A Collier; Barnes, J R; Mittag, M; Perdelwitz, V; Kohl, S
ABSTRACT: We present the first Doppler images of the prototypical active binary star RS Canum Venaticorum, derived from high-resolution spectra observed in 2004, 2016 and 2017, using three different telescopes and observing sites. We apply the least-squares deconvolution technique to all observed spectra to obtain high signal-to-noise line profiles, which are used to derive the surface images of the active K-type component. Our images show a complex spot pattern on the K star, distributed widely in longitude. All star-spots revealed by our Doppler images are located below a latitude of about 70°. In accordance with previous light-curve modelling studies, we find no indication of a polar spot on the K star. Using Doppler images derived from two consecutive rotational cycles, we estimate a surface differential rotation rate of ΔΩ = −0.039 ± 0.003 rad d −1 and α = ΔΩ/Ωeq = −0.030 ± 0.002 for the K star. Given the limited phase coverage during those two rotations, the uncertainty of our differential rotation estimate is presumably higher.